2021
DOI: 10.21203/rs.3.rs-872891/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of low-dose aspirin use among COVID-19 critically ill patients: A Multicenter Propensity Score Matched Study

Abstract: BackgroundMultiple medications with anti-inflammatory effects have been used to manage the hyper-inflammatory response associated with COVID-19. Aspirin is used widely as a cardioprotective agent due to its antiplatelet and anti-inflammatory properties. Its role in hospitalized COVID-19 patients has been assessed and evaluated in the literature. However, no data regards its role in COVID-19 critically ill patients. Therefore, this study aims to evaluate the use of low-dose aspirin (81-100 mg) and its impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…An observational study of mainly ICU critically ill patients suggested that aspirin therapy prior to hospitalization and continued during ICU stay was associated with lower mortality (HR ¼ 0.72 [0.52, 1.01]; p ¼ 0.05), but not when it was newly initiated (HR ¼ 1.22 [0.68, 2.20]; p ¼ 0.50). 78 However, another study on hospitalized patients aged 75 years or older did not show a survival effect but showed longer hospital length of stay in patients taking aspirin compared with those who were not (11 vs. 10 days, p ¼ 0.024), more likely to be transferred to ICU, (7.5 vs. 3.6%, p ¼ 0.007). 77 During the acute phase of the disease, the use of antiplatelet agents evaluated in the RECOVERY trial was not associated with a survival benefit (RR, 0.96; 95% CI, 0.89-1.04; p ¼ 0.35).…”
Section: Antiplatelet Therapiesmentioning
confidence: 96%
“…An observational study of mainly ICU critically ill patients suggested that aspirin therapy prior to hospitalization and continued during ICU stay was associated with lower mortality (HR ¼ 0.72 [0.52, 1.01]; p ¼ 0.05), but not when it was newly initiated (HR ¼ 1.22 [0.68, 2.20]; p ¼ 0.50). 78 However, another study on hospitalized patients aged 75 years or older did not show a survival effect but showed longer hospital length of stay in patients taking aspirin compared with those who were not (11 vs. 10 days, p ¼ 0.024), more likely to be transferred to ICU, (7.5 vs. 3.6%, p ¼ 0.007). 77 During the acute phase of the disease, the use of antiplatelet agents evaluated in the RECOVERY trial was not associated with a survival benefit (RR, 0.96; 95% CI, 0.89-1.04; p ¼ 0.35).…”
Section: Antiplatelet Therapiesmentioning
confidence: 96%
“…Data were abstracted by four authors (WS, HM, ZG, and QC) from 34 studies, (Abu-Jamous et al, 2020;Alamdari et al, 2020;Giacomelli et al, 2020;Lodigiani et al, 2020;Russo et al, 2020;Sahai et al, 2020;Tremblay et al, 2020;Chow et al, 2021a;Chow et al, 2021b;Connors et al, 2021;Fröhlich et al, 2021;Haji Aghajani et al, 2021;Ho et al, 2021;Kim et al, 2021;Liu et al, 2021;Meizlish et al, 2021;Merzon et al, 2021;Mura et al, 2021;Osborne et al, 2021;Pan et al, 2021;Sisinni et al, 2021;Son et al, 2021;Xiang et al, 2021;Yuan et al, 2021;Zhao et al, 2021;Zhou et al, 2021;Al Harthi et al, 2022;Santoro et al, 2022a;Chow et al, 2022;Formiga et al, 2022;Gogtay et al, 2022;RECOVERY Collaborative GroupAbbas et al, 2022; REMAP-CAP Writing Committee for the REMAP-CAP InvestigatorsBradbury et al, 2022;Sullerot et al, 2022), including three randomized controlled trials, (Connors et al, 2021;RECOVERY Collaborative GroupAbbas et al, 2022; REMAP-CAP Writing Committee for the REMAP-CAP InvestigatorsBradbury et al, 2022), 27 retrospective studies, (Abu-Jamous et al, 2020;Alamdari et al, 2020;…”
Section: Data Extractionmentioning
confidence: 99%